Employee training and development practices in the Tourism and Leisure sector in KwaZulu-Natal, South Africa. - Thembinkosi Mzimela; Christopher T. Chikandiwa (African Journal of Hospitality, Tourism and Leisure, 2017)
Employee training and development is imperative for every organisation. With effective training and development in place, organisations stand a chance of earning competitive edge in the business environment. The main objective of this article was to assess the effectiveness of the training and development practices on employee performance in the Tourism and Leisure Sector. Participants for the study were employees from different organisations in KwaZulu-Natal. Data were collected using the questionnaire which sought both quantitative and qualitative data. The results of the study indicated that most of the organisations surveyed did not have well-defined training and development plans. The findings also showed that ineffective training and development systems reduce the performance of the employees. As part of recommendations, it was suggested that organisations should consider needs assessment prior to training employees. It has also been noted that training and development plans, procedures and policies should be communicated to the employees for them to effectively contribute to the success of the organisations through striving towards achieving the objectives of their respective organisations.